PHYSICAL FITNESS OF FIREFIGHTERS IN THE CITY OF CERES: AN EXPERIENCE REPORT (CIPEEX, 2026)
Introduction: Military firefighters must be in excellent physical condition to ensure safety and efficiency in emergency situations. In this context, this experience report describes an activity carried out in partnership between Physical Education students at the Evangelical University of Goiás and the Ceres-GO Fire Department. Objective: To report and evaluate the physical fitness of firefighters and promote the integration of theory and practice. Methods: The activity took place on May 14, 2025, involving four firefighters and eleven students. Initially, institutional presentations and theoretical guidelines were provided on the tests applied: square (agility), push-ups and sit-ups (muscular endurance), and cardiorespiratory fitness. Results: The results showed times between 8 and 12 seconds in the agility test and repetitions ranging from 15 to 35 push-ups and 20 to 50 sit-ups. The estimated VO2max was greater than 32.6 for all participants, demonstrating good physical conditioning. The activity made it possible to identify individual strengths and weaknesses, guiding the development of personalized training plans. In addition to the physical benefits, the project promoted dialogue on training strategies and operational challenges, providing an enriching experience for the academics. Conclusion: It is concluded that actions such as this are fundamental for the physical improvement of firefighters and for the practical and contextualized training of future professionals, reinforcing the importance of periodic evaluations and training programs specific to the demands of public safety.
Keywords: physical fitness; cardiorespiratory fitness; fire department